QUARTZ SOLUBILITY IN H2O-NACL AND H2O-CO2 SOLUTIONS AT DEEP CRUST-UPPER MANTLE PRESSURES AND TEMPERATURES: 2-15 KBAR AND 500-900°C - Newton R.C.; Manning C.E. (My University, 2000)
The solubility of quartz in H2O-NaCl solutions was measured at 2, 4.35, 10 and 15 kbar and 500-900°C, and at NaCl concentrations up to halite saturation, usually greater than 75 wt.%. Quartz solubility was also measured in CO2-H2O solutions at 10 kbar and 800°C. Solubilities were determined by weight loss of ground and polished quartz crystal fragments which were equilibrated with solutions in Pt envelopes for one to four days and then rapidly quenched. Experiments at 2 kbar were made with externally heated cold-seal apparatus; higher pressure experiments were done in a 34 inch-diameter piston-cylinder apparatus with NaCl pressure medium and graphite heater sleeve. Equilibrium solubility was demonstrated in several ways, and the present results reproduce those of Manning (1994) in pure H2O at selected conditions.At pressures below 4 kbar, NaCl in solution causes an initial ''salting-in'', or quartz solubility enhancement, which, at 2 kbar and 700°C, persists to concentrations as great as 70 wt.% NaCl before quartz solubility again becomes as low as in pure H2O. The maximum solubility occurs at X(H2O) ~ 0.9 and is 50% higher than in pure H2O. At 4.35 kbar and 700°C, however, quartz solubility decreases slightly with initial NaCl concentration, and then begins to drop rapidly with increasing salinity beyond 45 wt.% NaCl. At 10 and 15 kbar there is a steep initial decline in silica molality at all temperatures in the range 500-900°C, leveling off at higher NaCl concentrations. There is thus a pronounced change in solution behavior with pressure, from initial salting-in below 4 kbar to monotonic salting-out above 5 kbar. This pressure-induced change in silica solubility parallels the sharp decrease in H2O activity in NaCl solutions in the same pressure range found by Aranovich and Newton (1996). Therefore, the pressure-induced change in silica solubility is inferred to be a consequence of the dissociation of the neutral NaCl° complex to Na+ and Cl- as solution densities increase above about 0.7 gm/cm3. At very high salinities, approaching halite saturation, the isobars of quartz solubility as a function of NaCl mole fraction at 700°C converge, indicating that, for hypersaline fluids having the constitution of molten salts, pressure has only a minor effect on quartz solubility.Quartz solubility at 10 kbar shows exponential decline with increasing salinity at all temperatures in the range 500°C to 900°C. This is the expected behavior of a two-component solvent, in which quartz is sparingly soluble in one component. At 10 kbar, isotherms of log silica molality versus H2O mole fraction are linear between X(H2O) = 1.0 and 0.5, but begin to curve to lower values at 900°C, where high salinities are attained before halite saturation occurs. This behavior implies that the solute silica species is a hydrate that becomes progressively destabilized at low H2O concentrations of the solvent. Plots of log silica molality versus log H2O activity suggest that the solute species is neutral H4SiO4 with no additional solvated H2O molecules, assuming no Na-SiO2 complexing.The solubility of quartz in CO2-H2O fluids at 800°C and 10 kbar is much smaller than in NaCl solutions at the same P,T and H2O activity. Thermodynamic analysis suggests that the solute species in CO2-H2O fluids is H4SiO4 with 1-3 solvated H2O molecules, which is similar to the solute behavior inferred by Walther and Orville (1983) in CO2 and Ar solutions with H2O at lower pressures.The present results show that SiO2 will partition very strongly into a concentrated salt solution in deep crust-upper mantle metamorphic and metasomatic processes, in preference to a coexisting immiscible CO2-rich fluid. The much greater permeability of silicate rocks for salt solutions than for CO2-rich solutions, together with the much higher solubility of silica-rich phases in the former, could be an important factor in geochemical segregation processes involving rising and cooling fluids of magmatic or metamorphic origin.